2013
DOI: 10.1186/gm500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epigenetic changes in survivors of preterm birth reveals the effect of gestational age and evidence for a long term legacy

Abstract: BackgroundPreterm birth confers a high risk of adverse long term health outcomes for survivors, yet the underlying molecular mechanisms are unclear. We hypothesized that effects of preterm birth can be mediated through measurable epigenomic changes throughout development. We therefore used a longitudinal birth cohort to measure the epigenetic mark of DNA methylation at birth and 18 years comparing survivors of extremely preterm birth with infants born at term.MethodsUsing 12 extreme preterm birth cases and 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
137
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(157 citation statements)
references
References 80 publications
18
137
1
1
Order By: Relevance
“…Cruickshank and colleagues performed one such study in 12 PTB cases and 12 matched controls. 28 They evaluated DNA methylation from blood at birth and at 18 years and observed substantial overlap with the PTB-associated CpGs we reported at birth. DNA methylation differences observed at birth were no longer associated with PTB status at 18 years for the majority of CpG sites examined, but they report 10 CpGs that continue to differ in methylation at both time points, suggesting the potential for a long-term epigenetic signature of PTB.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Cruickshank and colleagues performed one such study in 12 PTB cases and 12 matched controls. 28 They evaluated DNA methylation from blood at birth and at 18 years and observed substantial overlap with the PTB-associated CpGs we reported at birth. DNA methylation differences observed at birth were no longer associated with PTB status at 18 years for the majority of CpG sites examined, but they report 10 CpGs that continue to differ in methylation at both time points, suggesting the potential for a long-term epigenetic signature of PTB.…”
Section: Introductionmentioning
confidence: 70%
“…17,[22][23][24] Few studies have evaluated the epigenetics of PTB, and those that have focus mostly on those born preterm. [25][26][27][28] Other studies focus on the short-term and long-term consequences of PTB for the neonate, 1,[29][30][31][32] in part, because of interest in the developmental origin of health and disease (DOHaD) hypothesis. 32,33 We recently evaluated DNA methylation in leukocytes from African American umbilical cord blood samples and identified thousands of DNA methylation differences between preterm and term fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…Samples and the Infinium HM450 data set used in this study largely overlap with our published studies on preterm birth 15 and our longitudinal DNA methylation changes in twins. 16 Buccal samples used in this study were selected based on the availability of the materials and array data quality.…”
Section: Samples Used In This Studymentioning
confidence: 99%
“…Altered DNA methylation has been in adulthood in term-born individuals in association with exposure to an adverse prenatal nutritional environment,67 68 and changes in DNA methylation have been reported in ex-preterm individuals in adulthood 69. Whether these differences are identifiable at birth is unclear; a recent epigenome-wide study using DNA extracted from stored neonatal blood spots and blood from the same individuals at age 18 years identified differences in DNA methylation profiles between preterm and term individuals at birth but found that these largely resolved by adulthood, presumably reflecting immaturity in the preterm group 70. Nevertheless, some loci were identified which showed differential methylation at birth and at age 18, suggesting that such changes might potentially be useful as biomarkers of disease risk 70…”
Section: Potential Mechanismsmentioning
confidence: 99%